2009
DOI: 10.1128/aac.00803-09
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Culture Conditions in Chemical Library Screening Identifies Alternative Inhibitors of Mycobacteria

Abstract: In this study, application of a dual absorbance/fluorescence assay to a chemical library screen identified several previously unknown inhibitors of mycobacteria. In addition, growth conditions had a significant effect on the activity profile of the library. Some inhibitors such as Se-methylselenocysteine were detected only when screening was performed under nutrient-limited culture conditions as opposed to nutrient-rich culture conditions. We propose that multiple culture condition library screening is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…Bacteria are routinely grown, and antimicrobial screening conducted, under conditions optimized for growth in the laboratory (oxygenation, temperature, pH, nutrient availability), even though conditions under which the target organisms cause disease may differ considerably from laboratory conditions and in fact, may be ‘sub-optimal’ for growth (Cooper, 2013). Variations in screening conditions have been shown to identify different inhibitors both in target-based and phenotypic screens (Miller et al, 2009; Dunn et al, 2015). Furthermore, it has recently been shown that apparently simple antimicrobial killing assays are very sensitive to variations in culture conditions and bacterial growth phase (Harms et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria are routinely grown, and antimicrobial screening conducted, under conditions optimized for growth in the laboratory (oxygenation, temperature, pH, nutrient availability), even though conditions under which the target organisms cause disease may differ considerably from laboratory conditions and in fact, may be ‘sub-optimal’ for growth (Cooper, 2013). Variations in screening conditions have been shown to identify different inhibitors both in target-based and phenotypic screens (Miller et al, 2009; Dunn et al, 2015). Furthermore, it has recently been shown that apparently simple antimicrobial killing assays are very sensitive to variations in culture conditions and bacterial growth phase (Harms et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite enormous potential advantages, TB-WCS approaches are underutilized as a drug discovery strategy. While several important studies in the pathogenic prokaryotes Staphylococcus aureus and Mycobacterium tuberculosis have collectively established the validity of TB-WCS assays to discover on-target chemical probes ( 6 , 23 , 24 ), each has been restricted by several technical issues that have limited efficiency, sensitivity, and/or throughput of the screens. The approach described here builds upon previous efforts but also incorporates several technological advances that improve sensitivity and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A bacteriostatic assay was set up as previously described [12], with cells added to give a final OD 600 of 0.05 . All extracts and controls were tested in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…The mycobacterial strains used were Mycobacterium smegmatis mc 2 155, M. bovis BCG (Pasteur) and M. tuberculosis H37Ra. M. smegmatis and M. bovis BCG were labelled with GFP through the introduction of the plasmid pSHIGH+hsp60 by electroporation and selection on media containing 50 μg/ml kanamycin as previously described [ 12 ]. GFP-labelled Staphylococcus aureus Newman was constructed as follows: the fdh (formate dehydrogenase) promoter was amplified from S. aureus Newman using Phusion™ Flash High-Fidelity PCR Master Mix (Finnzymes, Finland) according to the manufacturers' instructions with primers GGGGACAACTTTGTATAGAAAAGTTGgaaggggtaagtgtgataagc and GGGGACTGCTTTTTTGTACAAACTTgtctttaaaataagaagttcattaattgttc, where uppercase represents attB sites for Gateway cloning (Invitrogen) and lower case represents S. aureus DNA.…”
Section: Methodsmentioning
confidence: 99%